Institutional links to cope with school violence: an exploratory study - Maria das Graças Carvalho Ferriani; Diene Monique Carlos; Andressa Janerini Oliveira; Michelly Rodrigues Esteves; José Eurípedes Martins (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objective: Identify and analyze the institutional links of secondary schools to cope with school violence. Methods: Qualitative, descriptive and exploratory study, based on the concept of social network. Twelve secondary school administrators and coordinators were interviewed. The links established between the schools and other institutions were mapped using minimum maps of social institutional external network and semi-structured interviews. Data were analyzed through thematic content analysis. Results: The category "Mapping institutional links" showed important deficiencies in the institutional links between the studied schools and other sectors to cope with school violence. Conclusion: In methodological terms, the study considers social and institutional networks to cope with contemporaneous phenomena and presents important contributions to nursing, warning to current health needs of adolescents.